Surface modification of polymeric materials by cold atmospheric plasma jet - Kostov, Konstantin Georgiev [UNESP]; Nishime, Thalita Mayumi Castaldelli [UNESP]; Castro, Alonso Herman Ricci [UNESP]; Toth, A.; Hein, Luis Rogerio de Oliveira [UNESP] (Elsevier B.V., 2014)
In this work we report the surface modification of different engineering polymers, such as, polyethylene terephthalate (PET), polyethylene (PE) and polypropylene (PP) by an atmospheric pressure plasma jet (APPJ). It was operated with Ar gas using 10 kV, 37 kHz, sine wave as an excitation source. The aim of this study is to determine the optimal treatment conditions and also to compare the polymer surface modification induced by plasma jet with the one obtained by another atmospheric pressure plasma source the dielectric barrier discharge (DBD). The samples were exposed to the plasma jet effluent using a scanning procedure, which allowed achieving a uniform surface modification. The wettability assessments of all polymers reveal that the treatment leads to reduction of more than 40 degrees in the water contact angle (WCA). Changes in surface composition and chemical bonding were analyzed by x-ray photoelectron spectroscopy (XPS) and Fourier-Transformed Infrared spectroscopy (FTIR) that both detected incorporation of oxygen-related functional groups. Surface morphology of polymer samples was investigated by Atomic Force Microscopy (AFM) and an increase of polymer roughness after the APPJ treatment was found. The plasma-treated polymers exhibited hydrophobic recovery expressed in reduction of the O-content of the surface upon rinsing with water. This process was caused by the dissolution of low molecular weight oxidized materials (LMWOMs) formed on the surface as a result of the plasma exposure. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Atmospheric pressure plasma jet; Polymer surface modification; Wettability; Low molecular weight oxidized material; Dielectric barrier discharge